2021
DOI: 10.3390/rs13122378
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spill Detection with Multiscale Conditional Adversarial Networks with Small-Data Training

Abstract: We investigate the problem of training an oil spill detection model with small data. Most existing machine-learning-based oil spill detection models rely heavily on big training data. However, big amounts of oil spill observation data are difficult to access in practice. To address this limitation, we developed a multiscale conditional adversarial network (MCAN) consisting of a series of adversarial networks at multiple scales. The adversarial network at each scale consists of a generator and a discriminator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 43 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Ref. [53] addresses the problem of training an oil spill detection model with limited data by proposing a multi-scale conditional adversarial network (MCAN) comprised of adversarial networks at multiple scales. The multi-scale architecture comprehensively captures both global and local oil spill characteristics, while adversarial training enhances the model's representational power through generated data.…”
Section: Advancements In Deep Learning Technologiesmentioning
confidence: 99%
“…Ref. [53] addresses the problem of training an oil spill detection model with limited data by proposing a multi-scale conditional adversarial network (MCAN) comprised of adversarial networks at multiple scales. The multi-scale architecture comprehensively captures both global and local oil spill characteristics, while adversarial training enhances the model's representational power through generated data.…”
Section: Advancements In Deep Learning Technologiesmentioning
confidence: 99%
“…[27] employs a random forest-like strategy, achieving superior classification accuracy without overfitting, even with much smaller training datasets than commonly studied in deep learning literature for image classification tasks. In [28], a multi-scale model was applied to detect oil spills on the sea surface, achieving accurate detection results with very few training samples. In [29], a training strategy involving mutual guidance was used to create a powerful hyperspectral image classification framework trained on a small dataset.…”
Section: Introductionmentioning
confidence: 99%
“…A contamination probability model of the oil-spill area over the Caspian region showed that the contamination probability is more than 50 % in the shoreline range of 464 km to 508 km [26]. Besides, Li et al [27] proposed a multiscale conditional adversarial network to identify the large area of oil-spill using ERS-1, ERS-2, and Envisat-1 satellite data. Similarly, an adversarial learning approach is implemented to forecast the wind field correction and oil-spill drift detection [28].…”
Section: Introductionmentioning
confidence: 99%